La deserción escolar en la escuela Manuel Aguirre del barrio Zamora Huayco de la ciudad de Loja, en el período septiembre 2013 a febrrero 2014 y la intervención del trabajador social - CABRERA CONTENTO, CARLOTA ELIZABETH (2015)
To tell Kisnerman (2005) "Social Work is the discipline that handles the causes and effects of social problems" In this perspective, the present investigation is a work that was to determine the underlying causes dropouts in the Manuel Aguirre School in the city of Loja, becoming one contrasting between existing theoretical basis and what is happening today in the context investigated. It has made visible the lack of commitment of parents and family for the upbringing and education of those in charge, leading to failure to attend classes and therefore the ignorance of the issues addressed, creating insecurity not only to education but also emotional in children, because they do not develop affection with their classmates. Also a number of problems that children go through, they who have been diagnosed real and responsible were identified. The use of suitable methods for the investigation has allowed the results obtained are the fundamental basis for a proposal for intervention from a social perspective, a proposal that contains an effective process of dialogue and conversation, thought processes all members of the community education, to identify conditions and consider alternative solutions that lead to good children and children living with what I'm sure will be fulfilling one of the professional principles such as social justice